Adverse Drug Reactions, still masquerading after all these years?. (February 2019) - Gray, Laurence A.; Routledge, Philip A.
Abstract : Summary: In this journal in 1976, Professor Duncan Vere suggested that some adverse drug reactions could behave as "masqueraders", sometimes evading detection for a considerable time after a medicine was introduced into clinical practice. Using contemporary examples, we illustrate why we believe the five main reasons he cited for adverse drug reactions masquerading in this manner remain just as relevant today. Although newer methods of investigation are increasingly contributing to improved surveillance, individual case reports and spontaneous reporting systems for suspected adverse drug reactions remain a cornerstone of pharmacovigilance and should continue during the whole of the time that medicines continue to be used therapeutically.